2020
DOI: 10.1038/s41467-020-18674-4
|View full text |Cite
|
Sign up to set email alerts
|

Publisher Correction: ITGB3-mediated uptake of small extracellular vesicles facilitates intercellular communication in breast cancer cells

Abstract: An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Interestingly, these BAF-modulated integrins were also modulated after single inhibition of ARID1A or ARID1B, but to a lesser extent (Figure S7D), further highlighting the need for simultaneous inhibition of both proteins for full achievement of BAF inhibition effects. The functional consequences of this epigenetic event were supported by the protein reduction of the two most repressed integrins, namely, ITGB3 and ITGA9 (Figure 3G), both of which have been previously implicated in metastasis [36,37], as well as the clear repressive effect observed on transcriptional signatures related to the activation of integrin signalling (Figure S7E) and protein downregulation of key structural components of downstream pathways such as SRC or ILK, the last of which was transcriptionally and epigenetically repressed (Figure S7F-I).…”
Section: Baf Complex Disruption Promotes the Epigenetic Repression Of...mentioning
confidence: 69%
“…Interestingly, these BAF-modulated integrins were also modulated after single inhibition of ARID1A or ARID1B, but to a lesser extent (Figure S7D), further highlighting the need for simultaneous inhibition of both proteins for full achievement of BAF inhibition effects. The functional consequences of this epigenetic event were supported by the protein reduction of the two most repressed integrins, namely, ITGB3 and ITGA9 (Figure 3G), both of which have been previously implicated in metastasis [36,37], as well as the clear repressive effect observed on transcriptional signatures related to the activation of integrin signalling (Figure S7E) and protein downregulation of key structural components of downstream pathways such as SRC or ILK, the last of which was transcriptionally and epigenetically repressed (Figure S7F-I).…”
Section: Baf Complex Disruption Promotes the Epigenetic Repression Of...mentioning
confidence: 69%
“… 35 , 36 A number of related receptors and adhesion molecules on EV surface and recipient cells have been identified, including tetraspanins, integrins, proteoglycans, lectins, lipids, intercellular adhesion molecules and extracellular matrix components. 37 , 38 KIM-1 is originally identified as an early biomarker of renal proximal tubule injury. Recently, it has been confirmed that KIM-1 can function as a receptor recognizing PS, 39 oxidized low-density lipoprotein, 39 LMIR5/CD300b, 40 apoptosis inhibitor of macrophage, 41 and fatty acid.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that EVs may be internalized by host cells by clathrin-independent endocytosis, especially caveolae-dependent endocytosis. , However, different types of cells may differ in the specific mechanism of EV uptake. On the other hand, proteins localized on the surface of EVs, such as integrins and proteoglycans, play a vital role in the internalization of EVs . Research indicated that glycans in the surface of EVs could bind to the cellular chemokine receptor CCR8 via a bridging chemokine .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, proteins localized on the surface of EVs, such as integrins and proteoglycans, play a vital role in the internalization of EVs. 43 Research indicated that glycans in the surface of EVs could bind to the cellular chemokine receptor CCR8 via a bridging chemokine. 44 The functional status of recipient cells also could influence the uptake of EVs.…”
Section: Conclusion Msc-derivedmentioning
confidence: 99%